Analisa Keseragaman Distribusi Kekerasan Material AISI 4140 pada Produk Coran Crusher Tip - Yadi Hidayat, Reza; Sambas, Achmad; Abdulah, Epan (JTRM (Jurnal Teknologi dan Rekayasa Manufaktur), 2022)
Crusher Tip is one component in a shredder machine which has a primary function as a destroyer of mined rock as raw material for cement. The function requires Crusher Tip has toughness and high wear resistance. Several ways have been made ranging from reconditioning by welding and the development of manufacturing components with a suitable material. AISI 4140 material selection is the result of previous studies which concluded that the material is suitable as a material component Crusher Tip. However, the value in the study of violence reaches 25 HRC, where the value is still below the desired hardness value. The expected value of hardness for AISI 4140 material is above 40 HRC. The study was conducted on existing castings product, by reviewing previous research data and will make the process of re-heat treatment (Repair Heat treatment), with a variation of tempering temperature 205oC and 380oC. Then analyzed the mechanical properties and microstructure of materials, shows the increase in hardness. Results of the study can be used as a reference for a suitable heat treatment process on AISI 4140 material.